The Influence of Live Streaming and Online Customer Reviews on Purchase Decisions on Tiktok Shop - Andien Muhzianareva; Lis Tatin Hernidatiatin (International Journal Labs, 2026)
The development of social media–based e-commerce is driving changes in customer behavior when shopping. One example is TikTok Shop, which relies on live streaming and online customer reviews. However, differences remain in the level of consumer confidence when making purchasing decisions. Therefore, this study aims to analyze the influence of Live Streaming and Online Customer Reviews on Purchase Decisions on TikTok Shop. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The research sample consisted of 120 respondents who were TikTok Shop users and had purchased products, watched live streams, and read product reviews. SmartPLS was used to analyze data collected through questionnaires using a Likert scale. The results of the study show that Live Streaming has a positive and significant effect on purchase decisions, with a coefficient of 0.572. In addition, Online Customer Reviews have a positive and significant effect, with a coefficient of 0.370 on purchase decisions. Both variables simultaneously account for 78.8% of the variation in purchase decisions. The results indicate that the interactive experience provided through live streaming and the information derived from consumer reviews are important factors in purchase decisions on TikTok Shop. This study is expected to help businesses and platform developers improve their digital marketing strategies, particularly by managing consumer reviews and optimizing live-streaming features.